(3eMGSHI GdTQcGJ GdeYebI (B:s (3OQhS hJeGQjf eMdhdI (B/s - (3NebGfj, HOQ GdReGf s ((3GdLRGFQ(B: s (3GdfTQ GdLGeYj GdLOjO(B, s, 2021)
(3jhLg gPG GdcJGH Edi WdHI GdYdhe GdeGdjI hGdeMGSHjI HTcd YGe hWdHI GdeGSJQ heSGHbGJ GdOcJhQGg HTcd NGU, hgh jJfGhd GdYOjO ef GdehGVjY GdegeI aj ebjGS eMGSHI GdTQcGJ GdeYebI Ydi ZQGQ GdeYGdLI GdeMGSHjI daGQb GdEOeGL GdChd hechfGJg (B((3aGQb GdGfJbGA(B) (3haGQb GdJbjje(B) (3HdZI bGfhfjI heMGSHjI hab GdfXGe GdeMGSHj GdeGdj hGdeYjGQ GdOhdj dEYOGO GdJbGQjQ GdeGdjI Qbe (B03 IFRS (3, HGdGVGaI Edi fSH GdQbGHI hGdaGFOI aj GdeLeY, hehVhY GdbhGFe GdeGdjI GdehMOI hab GdfXGe GdeMGSHj GdeGdj hGdeYjGQ GdOhdj dEYOGO GdJbGQjQ GdeGdjI Qbe (B1OIFRS.s
(3GdeQGLY U(B.259 s
Keywords: (3GdeMGSHI GdeYebIs; (3eMGSHI GdTQcGJs